Remediation of Mind (ReMind) as Early Intervention in First Episode Psychosis - Shuib, Naniyati; Ahmad, Mahadir; Osman, Zubaidah Jamil; Alwi, Muhammad Najib Mohamad (International Journal of Psychosocial Rehabilitation, 2020)
The Remediation of Mind (ReMind) through targeted processing speed (PS) training module was adapted from the Neuropsychological and Educational Approach to Remediation (NEAR) and metacognitive strategies to suit the patients with First Episode Psychosis (FEP). The study aims to validate and evaluate the effectiveness of thecognitive remediation (CR) module in ameliorating cognitive deficits and social dysfunctions. The content validity was assessed by 3 expert psychiatrists and psychologists followed by reliability analysis. ReMind was tested in a randomized controlled trial with 30 participants with FEP who were assigned to the CR programme from 2 hospitals in Malaysia. The design process led to a useful tool, which strongly supported by the experts. The results demonstrated good content validity with validity coefficient of .89 and reliability (α= .87). The significant improvement in the baseline and post test scores of participants after completed the intervention indicate that ReMind module is effective and feasible as an evidence-based treatment for FEP. The module contributes as CR learning guidelines in rehabilitation which enlightens the therapist’s role and cognitive skills to facilitate an impactful recovery in schizophrenia in Malaysia. The findings imply its potential to be implemented as adjunct CR in enhancing global cognition and functional outcomes effectively. This study recommends a ReMind module which benefits the mental health professionals in psychiatric rehabilitation as a promising direction for future cognitive health of schizophrenia in Malaysia.